Effect of Growth Media on Plumule Emergence and Early Seedling Growth of Monodora myristica - Chinwe I. Saani; Joshua Kayode; Benson O. Ademiluyi; M. Yoserizal Saragih (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
The study investigated the emergence and early seedling development of Monodora myristica in six different growth media viz: mixture of river sand/top soil, river sand/saw dust, top soil/saw dust, saw dust only, top soil only and river sand only. Results obtained recorded highest percentage germination (63%) in seeds sown in saw dust only. Early seedling growth was observed for four months. The results of this study showed that seedlings sown in mixture of top soil/saw dust recorded highest mean plant height (16.83cm), stem girth ( 2.50mm), and leaf area (46.18cm2) at the end of the experimental time. Seedlings on top soil only had the highest number of leaves (3.89). River sand had the least seedling performance in all the growth parameters examined; plant height (13.27cm), stem collar girth (1.99mm), leaf length (8.61cm), leaf width (4.77cm) and leaf area (30.83cm2). The study established that the % emergence of Monodora myristica seedlings was best in saw dust medium while mixture of top soil/saw dusts is recommended for enhancing early seedling growth of this plant in the nursery.